Social policy advice to countries from the International Monetary Fund during the COVID-19 crisis: Continuity and change - Shahrashoub Razavi; Helmut Schwarzer; Fabio Durán Valverde; Isabel Ortiz; Devika Dutt (International Labour Organization (ILO), 2021)
The COVID-19 pandemic has caused massive disruptions to the global economy and forced policymakers to respond to the newly created challenges. Many policy institutions have therefore had to rethink their established approaches and their usual policy responses. @This paper explores whether there has been a change in International Monetary Fund (IMF) policy advice and conditions in its loan programmes and Article IV surveillance by examining the 148 country reports for IMF programmes in 2020, in the context of significant shifts in its global macroeconomic policy framework during the COVID-19 pandemic. It documents the policy recommendations made in these reports and finds that the IMF has supported increased expenditure on health care and cash transfer programmes, often on a temporary basis, even when it meant higher fiscal deficit and public debt. However, it also finds that the IMF has supported fiscal consolidation and reduction of public debt even more frequently, in 129 of the 148 reports examined. This seems to corroborate the findings of a number of recent studies. Given the pronounced gaps in social protection coverage, comprehensiveness and adequacy across all countries, it is essential that the measures taken to cope with the emergency do not remain a mere stopgap response, but progressively lead to the establishment or strengthening of rights-based national social protection systems, including floors. To do so, countries can and should pursue diverse financing options that are equitable in order to mobilize the financial resources needed for social investments, including investments in social protection systems and quality public services.
Keywords: I3; H6; H53; H55; 330; social protection; social security systems; social protection floors; child allowances; maternity benefits; disability benefits; social pensions; social health protection; social security contributions; public expenditure; fiscal space; domestic resource mobilization; official development assistance (ODA); developing countries; Sustainable Development Goals (SDGs)